Case report of a patient with Morbus Hirayama - presentation, diagnosis and differential diagnostic aspects - Teodor Angelov; Teodora Chamova; Dora Zlatareva; Nevena Fileva; Ivan Barbov; Ivailo Tournev (Bugarian Society of Neurology, 2021)
Hirayama disease, also known as monomelic amyotrophy, is a rare disease characterized by slowly progressive muscle weakness and atrophy in one upper limb, most commonly in the muscles groups of the forearm and wrist. In addition to taking a detailed neurological status, electromyography (EMG) and magnetic resonance imaging (MRI) of the cervical region, native and after contrast enhancement of the image, in a neutral position and flexion, play a key role in the diagnosis process. In terms of differential diagnostic, more common disorders such as amyotrophic lateral sclerosis (ALS), spinal muscular atrophy (SMA) and advanced carpal tunnel syndrome should be considered. We report „Hirayama disease” in a 16-year-old female who presented with gradual right upper limb weakness and wasting in the distal muscles, that was confirmed by electrophysiological and neuroimaging studies.
Keywords: Hirayama disease; phenotype